Against heterologous human fertilization - Fiori, Angelo (Medicina e Morale, 1997)
The process of the progressive acceptance of heterologous human "in vitro" fertilization may encourage its opposers to abandon their position, acknowledge its essential uselessness and accept the principle according to which the products of progress should be available to anyone who wishes to use them. On the other hand the author believes that there are defects in artificial fertilization as a whole, not only in heterologous fertilization with its problems. Those involved are now attempting to hide these defects but they will soon undermine the certainties which up to now have been presented in the usual terms of biomedical triumphalism. In fact, artificial fertilization raises many scientific and ethical problems: the nature of heterologous fertilization treatment, risks for the mother and fetus, anonimity for the donor and risks of eugenetic selection as a consequence of the progress of molecular genetics, the children's rights, cryopreservation of the spare embryos and the hypothesis of "embryo donation". Today it is not possible to foresee the future of artificial fertilization and particularly heterologous fertilization. Nonetheless, the author expects that it will soon disappear because of the increasingly complicated problems involved. There has to be the maximum desire for a child and in fact the biological laws inspire this powerful desire, but heterologous fertilization with an anonymous father is not the answer to these hopes. There are other paths.